The Complexities between Nominee and Legal Heir : Bangladesh Context - Tamanna, Tamanna-E-Nur (JUSTICES: Journal of Law, 2025)
In Bangladesh, the idea of a nominee and nomination has actually been existing for centuries. Despite its extensive background, it is regrettable that the Act does not contain a uniform and unambiguous clause pertaining to a nominee's legal status. There is some ambiguity because of the intricate interactions and discrepancies between judicial rulings and legislative measures. In the lack of clear legislative direction, the court's discretion is typically used to resolve problems pertaining to the nominee's legal standing. The ultimate result is deprivation of rights of legal heirs in banking sector, capital market and everywhere. Instead of having constitutional safeguard the lacking of uniform law creates ambiguity to obtain rights in effective way. To ensure justice the Government should scrutinize the matter properly and should develop a suitable system in everywhere where the nominee and legal heir dispute arises.